New onset refractory status epilepticus: Long-term outcomes beyond seizures - Espino, Poul H.; Eschbach, Krista; Blank, Leah J.; Cervenka, Mackenzie C.; Muscal, Eyal; Farias-Moeller, Raquel; Gilmore, Emily J.; Gopaul, Margaret T.; Haider, Hiba A.; Hanin, Aurelie; Hirsch, Lawrence J.; Kellogg, Marissa A.; et al. (Epilepsia, 2025)
We propose and prioritize important outcome domains that should be considered for future research investigating long-term outcomes (LTO) after new onset refractory status epilepticus (NORSE). The study was led by the international NORSE Institute LTO Working Group. First, literature describing the LTO of NORSE survivors was identified using a PubMed search and summarized to identify knowledge gaps. Subsequently, a consensus-building process was performed to prioritize and rank important LTO domains for further research. The prioritization of LTO domains was qualitative, enabling the expert panel to generate ideas, share opinions, and provide reasons for the rankings. A second round took place to allow expansion and agreement regarding specific details for each domain. Outcomes were classified into eight main domains: (1) Function: Neuropsychological, Neurological (other than seizures), and Psychiatric (mood and behavior); (2) Quality of Life; (3) Epilepsy; (4) Nonneurological (medical); (5) Social; (6) Caregiver Burden; (7) Long-Term Mortality; and (8) Health Care System Impact. In addition, the working group suggested obtaining outcome measures for each domain at 6 months and 1 year after discharge and annually thereafter until stability has been reached. There are no currently established time frames set for when LTO in NORSE begin or plateau, and previously there existed no consensus regarding which LTO should be considered. This consensus process identifies and recommends NORSE LTO domains that should be considered in future research studies to provide more consistent results that can be compared between studies. Survivors of NORSE should be evaluated serially and at fixed points over time to maximize our understanding of the recovery trajectory for all LTO domains. Establishing reliable and standardized data describing LTO (beyond seizures) after NORSE will support discussions with families during the acute stages, prognostication, the development of targeted management strategies for survivors, and future comparative research globally helping to identify biomarkers that may predict LTO.